Genome-wide identification of the mutation uderlying fleece variation and discriminating ancestral hairy species from modern woolly sheep - Demars, Julie; Cano, Ema Margarita; Drouilhet, Laurence; Plisson-Petit, Florence; Bardou, Philippe; Fabre, Stéphane; Servin, Bertrand; Sarry, Julien; Woloszyn, Florent; Mulsant, Philippe; Foulquier, Didier; Carriere, Fabien; et al. (Oxford university press, 2017)
The composition and structure of fleece variation observedin mammals is a consequence of a strong selective pressure for fiber production after domestication. In sheep, fleece variation discriminates ancestral species carrying a long and hairy fleece from modern domestic sheep (Ovis aries) owning a short and woolly fleece.Here, we report that the “woolly” allele results from the insertion of an antisenseEIF2S2retrogene (calledasEIF2S2)intothe3 0 UTR of theIRF2BP2 gene leading to an abnormal IRF2BP2 transcript. We provide evidence that this chimeric IRF2BP2/asEIF2S2 messenger 1) targets the genuine sense EIF2S2 RNA and 2) creates a long endogenous double-stranded RNA which alters the expression of both EIF2S2 and IRF2BP2 mRNA. This represents a unique example of a phenotype arising via a RNA-RNA hybrid, itself generated through a retroposition mechanism. Our results bring new insights on the sheep population history thanks to the identification of the molecular origin of an evolutionary phenotypic variation.